Organizational creativity as idea work: Intertextual placing and legitimating imaginings in media development and oil exploration. (August 2019) - Håkonsen Coldevin, Grete; Carlsen, Arne; Clegg, Stewart; Pitsis, Tyrone S; Antonacopoulou, Elena P
How do we understand the nature of organizational creativity when dealing with complex, composite ideas rather than singular ones? In response to this question, we problematize assumptions of the linearity of creative processes and the singularity of ideas in mainstream creativity theory. We draw on the work of Bakhtin and longitudinal research in two contrasting cases: developing hydrocarbon prospects and concepts for films and TV series. From these two cases, we highlight two forms of work on ideas: (i) intertextual placing, whereby focal ideas are constituted by being connected to other elements in a larger idea field; and (ii) legitimating imaginings, where ideas of what to do are linked to ideas of what is worth doing and becoming. This ongoing constitution and legitimating is not confined to particular stages but takes place in practices of generating, connecting, communicating, evaluating and reshaping ideas, which we call idea work. The article contributes to a better understanding of the processual character of creativity and the deeply intertextual nature of ideas, including the multiplicity of idea content and shifting parts–whole relationships. Idea work also serves to explore the neglected role of co-optative power in creativity.